Upregulation of microRNA135a-3p and death receptor 5 plays a critical role in Tanshinone I sensitized prostate cancer cells to TRAIL induced apoptosis - Shin, Eun Ah (Impact Journals LLC, 2014)
Though tumor necrosis factor related apoptosis inducing ligand (TRAIL) has been used as a potent anticancer agent, TRAIL resistance is a hot-issue in cancer therapy. We investigated the antitumor mechanism of Tanshinone I to sensitize prostate cancer cells to TRAIL. Comibination of Tanshinone I and TRAIL exerted synergistic cytotoxicity, increased cleaved PARP, sub G1 population, the number of TUNELpositive cells, activated caspase 8, 9 and ROS production in PC-3 and DU145 cells. Of note, combination of Tanshinone I and TRAIL enhanced the protein expression of death receptor 5 (DR5) and attenuated anti-apoptotic proteins. RT-PCR and RT-qPCR analyses confirmed that co-treatment of Tanshinone I and TRAIL up-regulated DR5 and microRNA 135a-3p at mRNA level or activity of DR5 promoter and attenuated phosphorylation of extracellular signal regulated kinases in PC-3. Conversely, the silencing of DR5 blocked the increased cytotoxicity, sub G1 population and PARP cleavages induced by co-treatment of Tanshinone I and TRAIL. Interestingly, miR135a-3p mimic enhanced DR5 at mRNA, increased PARP cleavage, Bax and the number of TUNEL positive cells in Tanshinone I and TRAIL cotreated PC-3. Overall, our findings suggest that Tanshinone I enhances TRAIL mediated apoptosis via upregulation of miR135a-3p mediated DR5 in prostate cancer cells as a potent TRAIL sensitizer.